Implementasi Kantin Kejujuran dalam Menanamkan Karakter Jujur Anak Usia Dini - Nelly Agustina; Melly Indah Sari; Siti Hadjar; Nila Wardani Sihaloho (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Honesty is one of the fundamental character values that should be instilled from an early age to develop children into individuals with integrity, responsibility, and ethical behavior. One of the learning strategies that can be implemented to foster honesty is the honesty canteen, which provides children with direct experiences in practicing honest behavior in their daily activities. This study aims to analyze the implementation of the honesty canteen in instilling honest character among early childhood learners, identify supporting and inhibiting factors, and examine its implications for character education. This research employed a qualitative approach using the literature review method by examining various scientific articles, books, and relevant research reports related to honesty canteens, character education, and early childhood education. Data were analyzed using content analysis to identify key concepts, research findings, and patterns related to the implementation of honesty canteens. The findings indicate that the honesty canteen is an effective medium for developing honest character through habituation, responsibility, independence, discipline, and direct learning experiences. The successful implementation of the honesty canteen is influenced by teachers' commitment, parental support, school policies, and the consistency of character reinforcement in both school and home environments. Therefore, the honesty canteen can serve as an innovative and practical character education strategy for cultivating honesty from an early age